Selective N2-Alkylation of 1H-Indazoles and 1H-Azaindazoles - Clemens, Jennifer; Bell, Emily L.; Londregan, Allyn T. (Synthesis, 2022)
A general and selective procedure for the N2-alkylation of 1H-indazoles and 1H-azaindazoles is presented. Promoted by either trifluoromethanesulfonic acid or copper(II) triflate, diverse 1H-indazoles/azaindazoles are selectively alkylated with varied primary, secondary, and tertiary alkyl 2,2,2-trichloroacetimidates at the N2-nitrogen to afford the corresponding 2-alkyl-2H-indazoles/azaindazoles. Forty-one examples are included along with a discussion of reaction optimization, scope, and mechanism.
Keywords: regioselectivity; indazoles; alkylation; trichloroacetimidates; azaindazoles